ANALISIS IMPLEMENTASI SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA Pada PT Satria Perkasa Agung , Siak District Small , Bengkalis - ANDINI, FRINI KARINA; Herianto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to knows the implementation of health and safety management systems of work implemented by PT Satria Perkasa Agung ,Distrik Siak Kecil , Kabupaten Bengkalis, based on legislation in force , the Government Regulation No. 50 in 2012 on Health and Safety Management System of Work. This research is took a number of respondents as many as 65 people .The data obtained through questionnaires and interviews with key informance then further processed to be tested based on Government Regulation No. 50 in 2012 . So I can see the implementation of the system , management is Health and Safety PT Satria Perkasa Agung , Distrik Siak Kecil , Kabupaten Bengkalis, in accordance with Regulation No. 50 in 2012 .The results showed that the company has implemented a Health and Safety Management Systems Work under PP . 50 In 2012 , amounted to 88 % or a total of 147 items that have been implemented.Keyword : Implementation, Management Systems Occupational Health and Safety, Analysis